PENGGUNAAN BAHAN AJAR E-LEARNING BERBASIS PENDEKATAN INKUIRI UNTUK MEMBANTU SISWA MENCAPAI KETUNTASAN BELAJAR - Fatma Al Hamid (Molluca Journal of Chemistry Education (MJoCE), 2020)
Background of this development research is the less of student learning outcome as the result of the lack of educator in the East Babar island. The Purpose of this research is to develop e-learning based teaching materials at stoichiometry concept as an effort to solve the lack of teachers in the East Babar island. The first stage of this research is developing the teaching material at stoichiometry concept using ADDIE models and the second stage is to apply, it in terms of trial, to student. There are two types of the trial, first is to check the effect of this teaching material in a small group, and the second is to test it in the real sample. The trial of teaching materials uses One Group Pre-test and Post-test Design. Instruments of this research consist of validation instrument form (first step), observation form of the application of learning design; observation form of student activities; observation form of students’ affective, students’ responses form, and learning outcomes test. The obtained data at first step analyzed by using descriptive analysis, and for the second step analyzed by using statistical analysis. Result show that e-learning based teaching material that been develop is in good quality and ready to implementation in class